Conspiracist beliefs, intuitive thinking, and schizotypal facets: A further evaluation. Issue 6 (28th July 2020) - Denovan, Andrew; Dagnall, Neil; Drinkwater, Ken; Parker, Andrew; Neave, Nick
Summary: This study examined whether thinking style mediated relationships between belief in conspiracy and schizotypy facets. A UK‐based sample of 421 respondents completed the Generic Conspiracist Beliefs Scale (GCBS), Oxford‐Liverpool Inventory of Feelings and Experiences Short (O‐Life), and measures indexing preferential thinking style (proneness to reality testing deficits and Need for Cognition). Path analysis revealed direct and indirect relationships between Conspiracy Beliefs and schizotypy facets. Unusual Experiences had a direct effect on Conspiracy Beliefs and predicted Reality Testing and Need for Cognition. Preferential thinking style mediated the schizotypy‐belief in conspiracy relationship. This pattern of results (higher experiential‐based processing and lower Need for Cognition) was consistent with intuitive thinking. Introverted Anhedonia and Impulsive Nonconformity predicted Reality Testing and had indirect effects on Conspiracy Beliefs. Finally, Reality Testing predicted Conspiracy Beliefs, whereas Need for Cognition did not. These results confirm that cognitive processes related to thinking style mediate the schizotypy‐conspiracist beliefs relationship.